Workforce analysis of practicing rhinologists in the united states. (27th June 2019) - Heineman, Thomas E.; Ramakrishnan, Vijay; Hwang, Peter H.; Suh, Jeffrey D.
Abstract : Objectives: The objective of this study is to analyze the current rhinology workforce in the United States in terms of demographics, fellowship training, and regional distribution. Methods: The American Rhinologic Society (ARS) member database was queried for workplace zip code, age, gender, and fellowship training of practicing U.S. rhinologists through 2017. The San Francisco Match data were examined for rhinology fellowships from 2006 through 2017. Each rhinologist was assigned to a specific hospital referral region (HRR) determined by the Dartmouth Healthcare Atlas to assess geographic distribution and market density. Results: There were 296 ARS members self‐identifying as rhinologists. Of those, 69.2% were fellowship‐trained (FTR). The median age of FTRs and non‐FTRs were 41 and 54 years, respectively ( P < 0.001). Eighty percent of FTRs were male compared to 85.7% non‐FTRs. Given the recent growth of rhinology fellowships, the number of FTRs is currently expanding at approximately 16% per year. HRRs with the most rhinologists were Los Angeles, Boston, and Manhattan, all with 14. Approximately 100 million people live in HRRs without a practicing rhinologist. A wide variation in rhinologist density was observed, ranging from 133, 047 to 3, 636, 809 people per rhinologist, with a median of 747, 864. Conclusion: There may be a need for rhinologists in select parts of the country. Whereas the ARS database is likely an underestimation of the growing workforce, under current training rates we could pass the ideal number of U.S. rhinologists within 5 years. Level of Evidence: NA Laryngoscope, 130:1116–1121, 2020